Facile Synthesis of S/Ti3C2Tx Mxene@Se Cathode for High-Sulfur-Loading Lithium–Sulfur Batteries - Yupu Shi; Jianbin Xu; Xian Du; Yi Zhang; Fan Zhao; Ziwei Tang; Le Kang; Huiling Du (Batteries)
Lithium–sulfur batteries (LSBs) are gaining much attention because they offer a much higher theoretical energy density compared to traditional lithium-ion batteries. However, the cycling performance of LSBs with high sulfur mass loading is poor due to the shuttle effect, limiting the practical application of LSBs. In this work, a unique porous sulfur/Ti3C2Tx Mxene@selenium (S/Ti3C2Tx@Se) cathode of a LSB is synthesized by a simple hydrothermal method to address these challenges. In this composite, Ti3C2Tx forms a conductive framework and Se is tightly anchored on the framework. The Se inhibits the agglomeration of Ti3C2Tx and prevents the collapse of Ti3C2Tx. The S/Ti3C2Tx@Se composite can adsorb lithium polysulfides (LiPSs) and suppresses the shuttle effect and volume changes during cycling, improving the cycling stability of LSBs with high S loading. A high capacity of 812.2 mAh g−1 at 0.1 C with 5.0 mg cm−2 sulfur mass loading after 100 cycles is obtained. This work could inspire further research into high-performance S host materials for high-S-loading LSBs.